Low amniotic uid index and the materno-fetal out come in 3rd trimester of pregnancy (Bangladesh Medical Journal, 2016)
Amniotic fluid volume is an indirect indicator of fetal well being. About 8% of pregnant women can have low amniotic fluid, with about 4% being diagnosed with oligohydramnios. Oligohydramnios can cause complications in about 12% of pregnancies that go past 41 wks of gestation. This cross-sectional observational study was carried out in the Department of Obstetrics and Gynaecology, BSMMU, Dhaka from July 2010 to December 2010 on 55 admitted pregnant mother of 28-40 weeks gestational age with low amniotic fluid index (